The role of language and culture in face and scene processing and description strategies - Lee, Ai-Suan (2018)
Face perception is important in a variety of human social interactions, allowing us to keep track of individuals’ identities, recognise emotional expressions and intentions and make judgements about variables such as age, ethnicity and health. While early research assumed that face recognition strategies were universal, more recent studies have shown that East Asian and White Caucasian observers use different looking strategies to recognise faces, with East Asian participants focusing more on the centre of the face, which has been interpreted as representing a configural processing strategy, while White Caucasian observers fixate more on the eyes and mouth, which has been interpreted as representing a more featural processing strategy. Debate continues over the reasons behind this difference, with some researchers arguing that it represents an extension of more holistic cognition in the more collectivist East Asian cultures, and more analytic cognition in individualist Western cultures. The Sapir-Whorf hypothesis suggests that cognition is bound by language, and there have been studies showing changes in response patterns in tasks conducted by bilingual participants in their different languages. Others argue that these differences in face processing are driven instead by different salient diagnostic features of faces of different ethnicity. In this thesis, I present the results of five studies examining the role of culture and facial appearance in determining the looking strategy of East Asian and White Caucasian observers.